Mutation analysis of POLE gene in patients with early-onset colorectal cancer revealed a rare silent variant within the endonuclease domain with potential effect on splicing - Lasabová, Zora; Kalman, Michal; Holubeková, Veronika; Grendár, Marián; Kašubová, Ivana; Jaške, Karin; Meršáková, Sandra; Malicherová, Bibiana; Baranenko, Denis; Adamek, Mariusz; Kruzliak, Peter; Plank, Lukáš (Clinical and Experimental Medicine, 2019)
The colorectal cancer harbor germline, somatic or epimutations in mismatch repair genes, MUTYH or POLE gene, which lead to the hypermutated and ultramutator phenotypes with increased immune response. The mutations in POLE gene were reported to occur more frequently in early-onset colorectal cancer (EOCRC), and the patients are strong candidates for checkpoint inhibitor therapy. Here, we report mutation analysis within the endonuclease domain of the POLE gene in the cohort of patients with EOCRC in order to identify recurrent or new mutations and evaluate their association with the presence of tumor-infiltrating lymphocytes (TILs) and peritumoral lymphoid reaction. We have shown a significant association between MSI tumors and TILs (p = 0.004). Using sensitive single-tube nested PCR with subsequent Sanger sequencing, we have found in one female patient diagnosed at age 48 with rectal adenocarcinoma with mucinous elements staged pT3pN2pM1 a silent variant within the exon 9 NM_006231.3 c.849 C > T, NP_00622.2 p.Leu283 = recorded in dSNP as rs1232888774 with MAF = 0.00002. In silico prediction, result showed possible involvement into splicing; therefore, this rare variant can be involved into EOCRC pathogenesis. In the time of precise medicine, it is important to develop screening strategies also for less common conditions such as EOCRC allowing to predict tailored therapy for younger patients suffering from CRC that harbor mutations in the POLE gene.
Keywords: dospělí; proteiny vázající poly-ADP-ribosu; DNA Polymerase II; Humans; Mutation; lidé středního věku; Middle Aged; genotypizační techniky; mužské pohlaví; Adult; ženské pohlaví; kolorektální nádory; Genotyping Techniques; Poly-ADP-Ribose Binding Proteins; lidé; DNA-polymerasa II; mutace; Male; Colorectal Neoplasms; Female